Effect of Nanoclay on Thermal Properties of Polylacticacid-Clay Nanocomposite - Anuar, Hazleen; Kaiser, Mohammad Rejaul (2011)
At present polymer and their composites is one of the largest tonnage materials. But they become a headache day after day because of depletion of petroleum and pollution of environment. Biopolymer and their composites (like Polylacticacid (PLA) and its composites) can be a suitable competitor to replace convention polymers and composites. This paper focused on fabrication of PLA-based nanocomposite with different percentage of nanoclay and the effect of nanocaly on the thermal properties of nanocomposite. The result revealed that with addition of nanoclay glass transition temperature (Tg) and melting temperature (Tm) was increased 50C and 40C respectively. Dynamic mechanical analysis (DMA) showed that storage modulus and damping was increased with clay wherras TGA showed better degradation of PLA-Clay nanocomposite than PLA itself.